Я вирішила 2-ма . Обирай той, який більше підходить
Объяснение:
1). −6x^2−x+5=0
a=−6, b=−1, c=5
D=b^2−4ac=(−1)^2−4·(−6)·5=1+120=121
√D= 11
x1= −b+√D (дроб) 2a = −(−1)+11 (дроб) 2·(−6)= 12 (дроб) −12 =−1
x2= −b−√D (дроб) 2a = −(−1)−11 (дроб) 2·(−6) = −10 (дроб) −12 = 5 (дроб) 6
2). −6x^2−x+5=0
6x^2+x-5=0
6x^2+6x-5x-5=0
6x · (x+1) - 5(x+1)=0
(x+1) · (6x-5)=0
x+1=0
6x-5=0
x= -1
x= 5 (дроб) 6
В-дь: x1=−1
x2= 5 (дроб) 6
Я вирішила 2-ма . Обирай той, який більше підходить
Объяснение:
1). −6x^2−x+5=0
a=−6, b=−1, c=5
D=b^2−4ac=(−1)^2−4·(−6)·5=1+120=121
√D= 11
x1= −b+√D (дроб) 2a = −(−1)+11 (дроб) 2·(−6)= 12 (дроб) −12 =−1
x2= −b−√D (дроб) 2a = −(−1)−11 (дроб) 2·(−6) = −10 (дроб) −12 = 5 (дроб) 6
2). −6x^2−x+5=0
6x^2+x-5=0
6x^2+6x-5x-5=0
6x · (x+1) - 5(x+1)=0
(x+1) · (6x-5)=0
x+1=0
6x-5=0
x= -1
x= 5 (дроб) 6
В-дь: x1=−1
x2= 5 (дроб) 6